Comparison of live and fixed cell-based assay performance: implications for the diagnosis of MOGAD in a low-middle income country - Pandit, Lekha; D’Cunha, Anitha; Malli, Chaithra; Sudhir, Akshatha (Frontiers in Immunology, 2023)
Background Though considered optimal, live cell-based assay (LCBA) is often unavailable for the diagnosis of myelin oligodendrocyte glycoprotein antibody-associated disorders (MOGAD) in resource-poor regions. This study was undertaken to determine the agreement between LCBA and the widely available fixed cell-based assay (FCBA), for recommending testing guidelines within our region. Method All consecutive patients in our registry with a MOGAD phenotype were tested. The results from a commercially available FCBA (Euroimmun, Germany) were compared with a validated “in-house” LCBA. Clinical and MRI data were available for correlation. Results Among the 257 patient samples tested, 118 (45.9%) were positive by FCBA titre ≥1: 10 and or LCBA titres ≥1: 160 titre and 139 samples were negative. There was robust agreement between the two assays (agreement 98.8%, Cohen’s kappa 0.98 [95% CI- 0.95-1.00], Spearman correlation 0.97 (p < 0.0001). Among five discordant samples, four had clinical and or MRI data which supported an alternate diagnosis. There was a modest correlation between assay titres, particularly for samples with titres ≥ 1:100 in FCBA (Spearman’s Rho 0.26, p 0.005). Thirty samples were positive by FCBA at < 1:100 titre and included 1:80 (20),1:40(7) and 1:10 (3) titres. Among them, 80% had clear positive titres when tested by LCBA. Conclusion The FCBA tested with serum dilutions of 1:10 was highly predictive of MOGAD in our study and compared well with our “in-house” LCBA. The current recommendations for testing at higher dilutions need to be re-examined in light of our findings. The results of our study should ideally be replicated in a larger dataset but at the same time provide some guidance for the accurate diagnosis of MOGAD in resource-poor settings.